Transformational learning and identity shift: Evidence from a campus behind bars - Lerman, Amy E. (Punishment & society, 2023)
Identity-driven theories of desistance provide a useful model for understanding change in a carceral context. However, these theories often are not grounded in specific programmes or practices that might catalyze identity shift, and tend to focus narrowly on recidivism as the sole outcome of interest. In this study, we examine the role of prison higher education in identity-driven change through the process of transformative learning. Using administrative information on college-level course completion and an original longitudinal survey of prison college students, we show evidence of both between- and within-subjects shifts in individuals’ sense of self-efficacy, as well as their broader civic orientation. We further explore the role of identity using a survey experiment that randomly assigns individuals to a “student” versus “prisoner” identity label. We find that identity labelling has significant effects on both confidence in accomplishing one's goals and perceived likelihood of recidivism. We supplement these quantitative findings with qualitative interviews of prison college alumni. Our study suggests that access to higher education can be consequential for those in prison, and provides a broader framework through which to analyze the effects of prison programming that extends beyond recidivism.